2020
DOI: 10.3390/w12082176
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Channel Geometry on Different Water Quality Variables for Effective Designs and Waste Allocation Plans for Waterways

Abstract: It is necessary to study the parameters that affect water quality in order to devise mitigation measures if water quality would be at risk or negatively affected by those parameters. Those parameters are physical, chemical, biological, and hydraulic characteristics. This research will study the effect of channel geometry on different water quality variables, which is important in designing new irrigation canals in order to see how its geometry will affect water quality and lessen any negative impact if possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It was determined that the optimum conditions would be met in the case of 33% to 50% coverage of the canal. El Baradei [5] also analyzed the effect of channel geometry on different water quality variables for effective designs and waste allocation plans for waterways, with the Sheikh Zayed canal as the reference case study. The research revealed that concentrations of all water quality variables in water changed as a result of changing channel geometry.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…It was determined that the optimum conditions would be met in the case of 33% to 50% coverage of the canal. El Baradei [5] also analyzed the effect of channel geometry on different water quality variables for effective designs and waste allocation plans for waterways, with the Sheikh Zayed canal as the reference case study. The research revealed that concentrations of all water quality variables in water changed as a result of changing channel geometry.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…Solar power refers to the energy that is generated from the sun's light and heat, which can be captured using photovoltaic (PV) panels to convert sunlight into electricity (1). Unlike traditional fossil fuels, such as coal and natural gas, which are nite resources and have negative impacts on the environment, solar power does not emit greenhouse gases or other pollutants into the atmosphere (2). Solar power is considered an important alternative to traditional energy sources and an essential tool for reducing dependence on fossil fuels and promoting energy independence (3).…”
Section: Introductionmentioning
confidence: 99%